(4,4′-Dimethyl-2,2′-bipyridine-κ(2) N,N′)diiodidomercury(II) - Yousefi, Mohammad (International Union of Crystallography, 2008)
In the molecule of the title compound, [HgI(2)(C(12)H(12)N(2))], the Hg(II) atom is four-coordinated in a distorted tetrahedral configuration by two N atoms from the 4,4′-dimethyl-2,2′-bipyridine ligand and by two I atoms. There is a π–π contact between the pyridine rings [centroid–centroid distance = 3.775 (6) Å].